2019
DOI: 10.1371/journal.pbio.2005861
|View full text |Cite
|
Sign up to set email alerts
|

A temporal integration mechanism enhances frequency selectivity of broadband inputs to inferior colliculus

Abstract: Accurately resolving frequency components in sounds is essential for sound recognition, yet there is little direct evidence for how frequency selectivity is preserved or newly created across auditory structures. We demonstrate that prepotentials (PPs) with physiological properties resembling presynaptic potentials from broadly tuned brainstem inputs can be recorded concurrently with postsynaptic action potentials in inferior colliculus (IC). These putative brainstem inputs (PBIs) are broadly tuned and exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 59 publications
(129 reference statements)
2
11
0
Order By: Relevance
“…Our results clearly showed that neurons of FRA classes I and III with phasic responses had both the smallest latency jitter and jitter variation compared with neurons of other temporal responses of the same FRA class and with neurons of FRA class II ( Fig 12 ). The average values of first spike latency jitter of 0.367 ms (class I) and 0.560 ms (class III) were very similar to jitter values < 1 ms found in the ICC of the mouse [ 81 ], rat [ 82 ], cat [ 47 ], guinea pig [ 39 ], and bat [ 83 , 84 ]. These values of latency jitter were in the range of 0.1–1 ms as found in the auditory nerve and auditory cortex [ 65 ].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Our results clearly showed that neurons of FRA classes I and III with phasic responses had both the smallest latency jitter and jitter variation compared with neurons of other temporal responses of the same FRA class and with neurons of FRA class II ( Fig 12 ). The average values of first spike latency jitter of 0.367 ms (class I) and 0.560 ms (class III) were very similar to jitter values < 1 ms found in the ICC of the mouse [ 81 ], rat [ 82 ], cat [ 47 ], guinea pig [ 39 ], and bat [ 83 , 84 ]. These values of latency jitter were in the range of 0.1–1 ms as found in the auditory nerve and auditory cortex [ 65 ].…”
Section: Discussionsupporting
confidence: 73%
“…In conclusion, the above-mentioned mapping data about neuronal response properties in the ICC support the notion that auditory brainstem input is subject to some transformation in the ICC with enhancement of spectral resolution by degradation of timing precision and enhancement of timing precision by degradation of spectral resolution [ 46 , 47 ]. Neurons of FRA classes II and III appear to be representatives of such transformations, also with regard to transformation of auditory coding, by various aspects of neuronal responses, to certain local conditions in the ICC space [ 5 , 32 , 45 ].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…IC neurons are critically involved in processing important temporal features of sounds (Wenstrup et al, 2012 ; Chen et al, 2019 ; Yang et al, 2020 ). One striking biophysical property of IC neurons is rebound depolarization (Sun and Wu, 2008a ; Kasai et al, 2012 ; Chandrasekaran et al, 2013 ; Ayala and Malmierca, 2018 ).…”
Section: Discussionmentioning
confidence: 99%